Factors Affecting Job Satisfaction and Motivation: A Case Comparison of Generation Y and Generation Z in Bangkok - Chompukum, Pachsiry; Chakrapeesirisuk, Nattida (Creative Business and Sustainability Journal, 2020)
The objective of this study is to explore factors influencing job satisfaction and motivation of Generation Y members and Generation Z students in the Bangkok Metropolitan Area. The study used questionnaires to collect data from 390 respondents. Descriptive and inferential statistics, including factor analysis, reveal that both generations share similar work attitudes in most respects. Interestingly, Generation Z members value more highly jobs that provide opportunities to share challenging ideas, a greater work-life balance, and the motivating factor of self-happiness. The implications of the study can help organizations to enhance job satisfaction and motivation of Generation Y and Generation Z employees. In addition, the study contributes to the development of human resources management principles and practices.